INNV-40. REAL WORLD INTEGRATION OF THE NEUROLOGIC ASSESSMENT IN NEURO-ONCOLOGY (NANO) SCALE IN CLINICAL PRACTICE IN PATIENTS WITH IDH-WT GBM. (12th November 2021) - Lim-Fat, Mary Jane; Allen, Marie; Smith, Timothy; Youssef, Gilbert; Andersen, Brian; Akintola, Oluwatosin; Berger, Tamar; Budhu, Joshua; Hsieh, Annie; Aquilanti, Elisa; Batchelor, Tracy; Beroukhim, Rameen; et al.
Abstract: BACKGROUND: The neurologic assessment in neuro-oncology (NANO) scale was developed as a standardized metric to objectively measure neurologic function in patients with brain tumors and complement radiographic assessment in defining overall outcome. The scale has been incorporated in clinical trials. Early data is suggestive of feasibility and that NANO contributes to overall outcome assessment. However, real-world use of the NANO scale to drive clinical-decision making and the predictive value of the NANO scale to determine overall survival remains unclear in IDH-wt GBM. METHODS: We report on an ongoing study using the NANO scale to evaluate neurologic function in patients with IDH-wt GBM, seen at Dana-Farber Cancer Institute (DFCI). Patient demographics, tumor histology and molecular status, treatment history and progression dates are being captured. NANO score, as collected by a built-in scale in our institutional electronic medical record (EMR), functional status (Karnofsky performance status) and corticosteroid dose are collected at prespecified time points (prior to start of therapy, and during each subsequent MRI visit). Changes in the NANO score will be correlated to overall survival. Statistical analyses including descriptive data analysis and generalized linear models will be performed using R (version 3.4.3). RESULTS: Since June 2020, 50 patients have been enrolled in this study, including 42 (84%) with ≥2 follow up visits. Study accrual was initially impacted by the COVID-19 pandemic, but adaptation to a virtual platform for NANO allowed for improved recruitment and follow up of patients. Study results will be available for discussion at the 2021 SNO conference. CONCLUSIONS: Evaluation of neurologic function by NANO is feasible in a virtual framework in a prospective study in patients with GBM, aided by integration of the scale in our institutional EMR. NANO is able to objectively track neurologic function throughout disease course in IDH-wt GBM.